PROBLEMS IN PRESENTING THE FINANCIAL CONDITION OF AN ENDOWED COLLEGE OR UNIVERSITY. - Frisbee, Ira N. (The Accounting Review, 1930)
It is the purpose of this paper to consider problems encountered in attempting to portray the exact financial status of a college or university, and more particularly the endowed college or university. In preparing a balance sheet for an educational institution it will he observed that certain principles which are basic in all balance sheet presentation are applicable, whereas other principles are not. The purpose of any balance sheet is to set forth the assets and liabilities and the excess of assets over liabilities in the way which most clearly exhibits the financial condition of the institution. There are three main purposes which have been recognized for the assets of a college institution. Certain assets are held for use in a physical way; that is, as the educational plants. Other assets are held in the form of investments to produce income. This second group consists of the endowment assets, and they are to be maintained permanently as income producing investments. The third group of assets are those available for current purposes.